1992
DOI: 10.1176/ajp.149.10.1324
|View full text |Cite
|
Sign up to set email alerts
|

Melancholic/endogenous depression and response to somatic treatment and placebo

Abstract: Depressed patients with melancholia were not particularly different from depressed patients without melancholia in their responses to antidepressant medication but did differ from patients without melancholia in their responses to active medication versus placebo, particularly if their depression was moderate and not severe. This suggests that patients with DSM-III melancholia may be unresponsive to nonsomatic treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The naturalistic design of the study gives a special significance to this result as the majority of previous evidence comes from clinical trials comparing few antidepressant options and restricted inclusion criteria. The available data on melancholic depression favors tricyclic than narrow-action antidepressants [7], [38], [39]. A meta-analysis of 38 double-blind studies concluded that the reversible MAOI moclobemide have higher response rates in depressed patients with melancholic features[40].…”
Section: Discussionmentioning
confidence: 99%
“…The naturalistic design of the study gives a special significance to this result as the majority of previous evidence comes from clinical trials comparing few antidepressant options and restricted inclusion criteria. The available data on melancholic depression favors tricyclic than narrow-action antidepressants [7], [38], [39]. A meta-analysis of 38 double-blind studies concluded that the reversible MAOI moclobemide have higher response rates in depressed patients with melancholic features[40].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported differences in response rates based on diagnostic sub-groups, such as patients with melancholic depression showing better response to TCAs versus SSRIs (Roose et al, 1986) or patients with atypical depression responding better to MAOIs than to TCAs (Quitkin et al, 1993). However these findings are generally inconsistent (Peselow et al, 1992; Nelson et al, 1994) and the effects are small (Fava et al, 1997) indicating that treatment strategies based on diagnostic subgroups are unlikely to improve treatment efficacy. These efforts may prove to be more successful if the relative constellation of symptom features were evaluated as potential predictors of response.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic heterogeneity of most psychiatric disorders raises the possibility that some forms of illness may be more or less responsive to placebo-like interventions. For example, a study by Peselow et al [12]has shown lower placebo response rates in melancholic depression than in non-melancholic depression despite comparable response rates to active treatment in these two groups. However, attempts to restrict clinical trials to populations associated with lower placebo response rates are plagued by the same issues discussed above, in that pressure to enroll may affect some investigators’ diagnostic assessments and inflate the rate of diagnostic misclassification of subtypes of psychiatric disorders.…”
Section: The Search For a Culpritmentioning
confidence: 99%